Response to salinity stress in four Olea europaea L. genotypes: A multidisciplinary approach - Palm, Emily Rose; Salzano, Anna Maria; Vergine, Marzia; Negro, Carmine; Guidi Nissim, Werther; Sabbatini, Leonardo; Balestrini, Raffaella; De Pinto, Maria Concetta; Fortunato, Stefania; Gohari, Gholamreza; Mancuso, Stefano; Luvisi, Andrea; et al. (My University, 2024)
Despite a drought- and erosion-tolerant root system, olive trees are vulnerable to abiotic stress due to limited genetic variability. Though some olive cultivars are moderately tolerant to salinity stress, soil salinity is increasing in the semi-arid and arid regions where olive cultivation is common, significantly reducing overall production. In response, breeding programs may rely on proper selection markers for abiotic stresses, including salinity, but these are generally lacking for olive. Here, physiological and biochemical parameters were measured in four Olea europaea genotypes (Frantoio, Leccino, Lecciana, and Oliana) subjected to different intensities of salinity stress (0 mM, 100 mM and 200 mM NaCl). At moderate and high salt concentrations, Na+ exclusion, higher photosynthetic productivity and tissue water content in the tolerant cultivar Frantoio were linked with increased production of polyphenols, with more favorable K+/Na+ values (quercetin and rutin), mitigation of oxidative stress (oleuropein) and increased water absorption (luteolin). In Frantoio and Leccino, a significant change of the proteome repertoire occurred, with overrepresentation of components regulating cellular metabolism, ion transport, redox insult and dissipation of excess photochemical energy. Conversely, Lecciana and Oliana showed increased sensitivity to salinity stress in terms of photosynthetic parameters and elevated internal Na+ concentrations, together with the lowest number of differentially represented proteins. These results highlighted olive germplasm strategies to cope with osmotic stress, suggested a physiological and molecular basis for the augmented responsiveness of tolerant cultivars and identified specific biomarkers as useful targets for future breeding programs.
Keywords: Olive tree; Plant biodiversity; Plant physiology; Proteomics; Response to salt stress; Salinity